Cyber Resilience in Banking A Practical Guide to Governance, Risk, and Compliance. - Young, Richard Gwashy (Productivity Press, 2026)
Drawing on the authors' experience as a cybersecurity practitioner, technology risk leader, and educator, he has crafted this series to bridge the gap between theoretical frameworks and practical applications in banking security.